2012
DOI: 10.1097/pas.0b013e31823fa35b
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Lymph Node Harvest in Rectal Cancer (UICC Stages II and III) after Preoperative 5-FU–based Radiochemotherapy. Acetone Compression is a New and Highly Efficient Method

Abstract: The AC method is the method of choice for accurate LN staging in locally advanced rectal cancer, especially after preoperative RCT, and is well suited for routine gastrointestinal pathology workup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 63 publications
2
22
0
1
Order By: Relevance
“…For decades, fat clearance techniques have been the only approach to improve lymph node harvest in colorectal cancers. [18][19][20][21][22] We recently introduced the methylene blue-assisted lymph node dissection technique as a simple, cheap and very effective alternative method. Moreover, the usefulness of this technique has been approved by several other groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For decades, fat clearance techniques have been the only approach to improve lymph node harvest in colorectal cancers. [18][19][20][21][22] We recently introduced the methylene blue-assisted lymph node dissection technique as a simple, cheap and very effective alternative method. Moreover, the usefulness of this technique has been approved by several other groups.…”
Section: Discussionmentioning
confidence: 99%
“…17 Fat clearance is a well-known technique to improve lymph node harvest not only in colorectal cancer. [18][19][20][21][22] However, all of these techniques are time consuming, expensive and need potentially toxic agents. In 2007, we introduced the methylene blue-assisted lymph node dissection method as a cheap and simple alternative method to improve lymph node harvest in gastrointestinal cancers.…”
mentioning
confidence: 99%
“…It's necessary to discover efficient pathway to impede the ectopic proliferation and accelerate death of tumor cells. Although, broad-spectrum anticancer drug such as 5-FU (a pyrimidine analogue) is widely used for clinical therapy (Gehoff et al, 2012;Pera et al, 2012;Su, 2012), the large side effects which it has been shown are a still limit aspect for use. Luteolin, a natural dietary flavonoid isolated from various plants has the potential role to slow or prevent the growth of tumor cell lines (Ko et al, 2002;Ju et al, 2007;Lim, et al, 2007;Chiu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Cases with WME were prepared in a second pathological institution (Department of Pathology, University Medical Center Göttingen) as part of a study of LN retrieval after CRT in the context of the CAO/ARO/AIO-04 phase III trial 8 9 12. WME has been described previously 8…”
Section: Methodsmentioning
confidence: 99%
“…AC was performed as described in the literature 10 12. In brief, the tissue in the tumour region was cut in cross sections and checked for visible or palpable LN, that is, manual dissection of the tumour region was performed.…”
Section: Methodsmentioning
confidence: 99%